Sistema de geração de energia elétrica em tratores para aplicações agrícolas - Leão, Aline Rocha (2020)
The use of electrical energy in applications where historically only mechanical energy has been used has become a tendency today. This work proposes the development of two electrical power supply on the tractor from its Power Take-off (PTO). For the development of electrical outputs, it was necessary to study and then choose the generator with the desired characteristics. In the case of the chosen generator, a multiplier was necessary to correctly couple the generator to PTO. As the rotation of the PTO is not always constant, a form of control was designed, using a three-phase rectifier and boost converter together with an inverter to maintain the stability of the electrical power supply, regardless of the tractor's rotation. In this work, the control for one of the outputs is approached, being possible to activate a load of up to 1.5 and that can be replicated, later, to be used in the second output. Experimental tests of the power generator coupled to the tractor's PTO are presented, followed by the analysis, design and simulation of the control of the DC loop of one of the proposed electrical outputs.